Baris Kekupu di Banjar Lebah Desa Sumerta Kaja sebagai sumber inspirasi dalam Penciptaan Karya Seni Lukis - Putra Artawan, I Made; Karja, I Wayan; Setem, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2021)
Baris Kekupu Dance is a dance that was originally created to accompany the memukur/nyekah ceremony, which is during the mepurwa daksina process. The idea of creating the Baris Kekupu dance is from the butterfly decoration on the resin brackets that are found during the memukur ceremony. The Baris Kekupu dance has its own uniqueness and characteristics such as colorful costumes, wearing legong coils, and using the butterfly wing property which has an aesthetic value in terms of color. The meaning contained in the Baris Kekupu dance and its uniqueness has become an idea and source of inspiration for the author in painting. The method used in the research of the Baris Kekupu Dance in Banjar Lebah is the method of observation, interviews, literature, and documentation. The idea in this creation are realized by the author using the methods of exploration, experimentation, and formation. In the process of realizing this work, the author pours his ideas and imagination into canvas media. The author describes the object of the Baris Kekupu dance and its supporting objects by pouring the author’s imagination in accordance with the uniqueness and meaning contained in this dance, which the author manifest into six works, including: 1. The Birth of the Baris Kekupu Dance, 2. Pitra Yadnya, 3. Mepurwa Daksina, 4. Journey to Sunia Loka, 5. Towards Swarga Loka, 6. Towards Neraka Loka. In the creation of this work, the author applies the elements and principles of painting. The creation of paintings is viewed from the physioplastic and ideoplastic aspects. Then the writer is able to describe the meaning of the six works.